Engineering poly(lactic-co-glycolic acid)/hydroxyapatite microspheres with diverse macropores patterns and the cellular responses1. Issue 23 (13th March 2015) - Cheng, D.; Cao, X.; Gao, H.; Hou, J.; Li, W.; Hao, L.; Wang, Y.
<x xml:space="preserve">Abstract</x> Design macroporous topography on spherical substrates via a straightforward approach and investigate the corresponding cell responses.